ChemInform Abstract: Dual Hypervalent Iodine(III) Reagents and Photoredox Catalysis Enable Decarboxylative Ynonylation under Mild Conditions. Issue 43 (October 2015) - Huang, Hanchu; Zhang, Guojin; Chen, Yiyun
Abstract The first hypervalent iodine reagent (HIR)/photoredox dual catalysis to form radicals from α‐ketoacids, followed by an unprecedented acyl radical addition to HIR‐bound alkynes is presented.